Knowledge and Preventive Practices on Scrub Typhus among Caregivers Attending at Bharatpur Hospital, Chitwan, Nepal - Chaudhary, Tulasi; Sharma, Nita; Adhikari, Pratima; Parajuli, Sumitra (Journal of Bharatpur Hospital, 2025)
Background: Scrub typhus is a potentially fatal acute febrile illness can affect people of all ages and travellers across the globe who has visited regions of endemicity Assessing people’s knowledge and preventive practices of scrub typhus helps to prevent infected mites-related diseases. This study aimed to find out the scrub typhus knowledge and preventive practices of the people attending a Bharatpur Hospital.Methods: A descriptive cross-sectional study was conducted at Bharatpur Hospital, Chitwan, from June 2024. Consecutive sampling technique was used among 406 the people who met the inclusion criteria. The data were analysed in SPSS version 20, using descriptive as well as inferential statisticsResults: Among 406 participants, 53.0% and 54.4% participants had good level of knowledge and preventive practice, respectively. In the chi-square test applied to find the association between variables, participants’ age group of < 30 years (P < 0.006), service occupation (P < 0.018), bachelor and above education level (P < 0.024), and Brahmin/Chhetri (P < 0.030) were significantly associated with knowledge of Scrub Typhus.Conclusions: Overall, knowledge about scrub typhus and preventative practices were found to be good. Awareness programme on scrub typhus necessary to improve knowledge and practice among more than 30 years of age, agriculture worker and basic education and illiterate group.